A Young Crustal Component in the Caroline Mantle Plume (Western Pacific Ocean) - Yuan Zhong; Ji Zhang; Sanzhong Li; Guo‐Liang Zhang (Geophysical Research Letters)
Abstract The geochemical variability in oceanic island basalts is linked to Earth's deep mantle heterogeneity, with distinct mantle components whose origin is under debate. In this study, we found basalts from the Caroline Seamount Chain exhibit elevated δ57Fe signatures. The association of high δ57Fe with mildly depleted Nd–Hf isotope compositions indicates the involvement of a young crustal component in the Caroline plume, which was likely introduced into the Pacific Large Low Shear Velocity Province (LLSVP) by the subduction girdle surrounded Rodinia supercontinent about 600 million years ago. Similar recycled crustal components are also found in basalts from hotspots near the boundary of the Pacific LLSVP, including Hawaii and Galapagos, but not seen in basalts from hotspots centered in the Pacific LLSVP. We suggest the circum‐Rodinia subduction could lead to such preferential appearance of young crustal materials, and consequently result in the zoned compositional structure of the Pacific LLSVP.